2012
DOI: 10.3389/fphys.2012.00171
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Neuronal Survival Factor MEF2 by Kinases in Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is the second most common neurodegenerative disorder due to selective death of neurons in the substantia nigra pars compacta. The cause of cell death remains largely unknown. Myocyte enhancer factor 2 (MEF2) is a group of transcriptional factors required to regulate neuronal development, synaptic plasticity, as well as survival. Recent studies show that MEF2 functions are regulated in multiple subcellular organelles and suggest that dysregulation of MEF2 plays essential roles in the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 169 publications
0
35
0
Order By: Relevance
“…Another major target of ERK5 indirect transcriptional modulation is a group of transcription factors termed myocyte enhancer factor 2, which have been suggested to play a role in PD (Yin et al . ). The IFN‐γ–ERK5 pathway could also indirectly influence the LRRK2 promotor by inducing transcription factors that in turn activate LRRK2 expression.…”
Section: Discussionmentioning
confidence: 97%
“…Another major target of ERK5 indirect transcriptional modulation is a group of transcription factors termed myocyte enhancer factor 2, which have been suggested to play a role in PD (Yin et al . ). The IFN‐γ–ERK5 pathway could also indirectly influence the LRRK2 promotor by inducing transcription factors that in turn activate LRRK2 expression.…”
Section: Discussionmentioning
confidence: 97%
“…Dopaminergic cells are particularly susceptible to oxidative stress (Graham et al, 1978), while neurotrophic and anti-apoptotic factors can confer protection against environmental and genetic risk factors associated with PD pathogenesis (Mangano et al, 2011; Nagahara and Tuszynski, 2011; Rieker et al, 2012; Stahl et al, 2011; Yin et al, 2012). We showed that in cases of increased protection against 6-OHDA-induced death, such as following neuronal RNF11 knockdown, there is an associated increase in expression of (1) antioxidants GSS and SOD1, (2) neurotrophic factor BDNF and (3) anti- apoptotic factor BCL2.…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of MEF2 activity is complex. MEF2-dependent gene transcription depends not only on the nature of extracellular stimuli (McKinsey et al 2002) but also on the complement of MEF2 isoforms expressed within a cell (including alternatively spliced variants), isoform dimerization, regulated degradation and phosphorylation state (Ornatsky & McDermott 1996;Yin et al 2012). Indeed, phosphorylation and dephosphorylation of MEF2 regulate a large number of processes related to MEF2 function, including modulation of DNA-binding affinity, association with transcriptional coregulators or co-repressors, acetylation and sumoylation, nuclear and cytoplasmic trafficking and caspase-mediated degradation (Heidenreich & Linseman 2004;Li et al 2001;Shalizi et al 2006;Yin et al 2012) (Fig.…”
Section: Regulation Of Mef2 Activitymentioning
confidence: 99%